(3cJGH aj CUhd Yde GdfLhes - (3CMeO Hf eMeO Hf cKjQGdaQZGfj,J (B240 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdaUd GdChd ai Sfi GdYQH hGdYLe , hCSeGA TghQge hCjGege hGNJdGa eG Hjf HYVgG GdHYV s
(3BNQgG (B:s
(3hbO HjfG ef cSha GdTeS hGdbeQ eG ajg caGjI Ef TGA Gddg JYGdi s
(3Gdajde ZjQ ehLhOs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B220 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B10 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs